The outcome in patients with BRAF-mutated metastatic melanoma treated with anti-programmed death receptor-1 monotherapy or targeted therapy in the real-world setting - Kopecký, Jindřich; Pásek, Marek; Lakomý, Radek; Melichar, Bohuslav; Mrazová, Ivona; Kubeček, Ondřej; Arenbergerová, Monika; Lemstrová, Radmila; Švancarová, Alžběta; Tretera, Vojtěch; Hlodáková, Alžběta; Žváčková, Kamila (Cancer medicine, 2024)
BACKGROUND: Immunotherapy and targeted therapy are currently two alternative backbones in the therapy of BRAF-mutated malignant melanoma. However, predictive biomarkers that would help with treatment selection are lacking. METHODS: This retrospective study investigated outcomes of anti-programmed death receptor-1 monotherapy and targeted therapy in the first-line setting in patients with metastatic BRAF-mutated melanoma, focusing on clinical and laboratory parameters associated with treatment outcome. RESULTS: Data from 174 patients were analysed. The median progression-free survival (PFS) was 17.0 months (95% CI; 8-39) and 12.5 months (95% CI; 9-14.2) for immunotherapy and targeted therapy, respectively. The 3-year PFS rate was 39% for immunotherapy and 25% for targeted therapy. The objective response rate was 72% and 51% for targeted therapy and immunotherapy. The median overall (OS) survival for immunotherapy has not been reached and was 23.6 months (95% CI; 16.1-38.2) for targeted therapy, with a 3-year survival rate of 63% and 40%, respectively. In a univariate analysis, age < 70 years, a higher number of metastatic sites, elevated serum LDH and a neutrophil-lymphocyte ratio above the cut-off value were associated with inferior PFS regardless of the therapy received, but only serum LDH level and the presence of lung metastases remained significant predictors of PFS in a multivariate analysis. CONCLUSIONS: Present real-world data document the high effectiveness of immunotherapy and targeted therapy. Although targeted therapy had higher response rates, immunotherapy improved PFS and OS. While the prognostic value of LDH was confirmed, the potential use of blood cell count-derived parameters to predict outcomes needs further investigation.
Keywords: Receptors, Death Domain; nádory kůže; Proto-Oncogene Proteins B-raf; retrospektivní studie; lidé; protoonkogenní proteiny B-Raf; senioři; receptory domény smrti; melanom; Aged; Retrospective Studies; Skin Neoplasms; Melanoma; Humans